Identification of alternative-splicing events in human monocyte differentiation - Sim, Donald Yuhui (2018)
The alternative splicing of precursor messenger RNA is an important determinant of gene expression and has a prominent role in the development and homeostasis of immune cells. The splicing factor SRRM2 had been previously found by our group to be down-regulated during monocyte differentiation and the knock-down of SRRM2 enhances the expression of certain macrophage surface markers, although it and its binding partner SRRM1 remain relatively uncharacterised. Therefore, our lab had previously performed the depletion of these splicing factors in monocyte-like THP-1 cells and detected a large number of differential alternative splicing events through RNA-seq. The data obtained from RNA-seq still required verification through traditional methods, such as RT-PCR. During this project, 31 out of 47 splicing events were successfully validated, with SRRM2-regulated splicing events achieving a 92% validation rate. Additionally, gene set enrichment analysis (GSEA) also revealed potential perturbations in anti-viral, amino acid metabolism and intracellular signalling pathways by the knockdown of these splicing factors. Through a combination of the validation data and GSEA results, alternative splicing events in several key proteins involved in the immune-related nuclear factor-kappa B (NF-κB) signalling pathway were identified for consideration in further studies on the regulatory role of SRRM1 and SRRM2 in monocytes.